The interrelationships between the microRNA miR-34a and the plant flavonoids apigenin and quercetin in the regulation of ovarian cell functions - Alexander V. Sirotkin; Zuzana Fabová; Barbora Loncová; Zuzana Kislíková; Abdel Halim Harrath (Scientific Reports)
Abstract Our study aimed to examine the possible interrelationships between RNA interference and plant flavonoids in the regulation of ovarian functions. For this purpose, we compared porcine ovarian cells that were transfected or not with oligonucleotides to drive miR-34a overexpression (miR-34a mimics) and cultured in the presence of absence of apigenin or quercetin (at doses of 1, 10–100 µg/ml). The miR-34a expression, proliferation (proportion of PCNA-positive cells), cytoplasmic apoptosis (proportion of bax-positive cells), and secretion of progesterone, estradiol and insulin-like growth factor I (IGF-I) were analyzed by quantitative immunocytochemistry and enzyme-linked immunosorbent assay (ELISA). Transfection of cells with miR-34a mimics induced miR-34a overexpression and suppressed the proliferation, apoptosis, and secretion of estradiol but promoted the secretion of progesterone and IGF-I. In nontransfected cells, apigenin stimulated proliferation, inhibited apoptosis and progesterone and IGF-I secretion, but promoted estradiol secretion. Overexpression of miR-34a reversed the effect of apigenin on proliferation and apoptosis but the effect not on hormone secretion. Quercetin inhibited proliferation, apoptosis, and release of all measured hormones by nontransfected cells. In transfected cells, quercetin did not affect proliferation, did promote apoptosis, and did inhibit progesterone and IGF-I secretion, but it did not affect estradiol secretion. On the other hand, both apigenin and quercetin mitigated the main effects of miR-34a. Our observations demonstrate the roles of miR-34a, apigenin and quercetin in the regulation of basic ovarian cell functions. The ability of miR-34a to induce and reverse the effects of both apigenin and quercetin suggests that miRNAs can shape the response of healthy ovarian cells to plant molecules. On the other hand, plant molecules can weaken the effects of miRNAs on ovarian cells. The experiments in the current study are the first to demonstrate the mutual interrelationships between miR-34a and plant flavonoids in the regulation of healthy ovarian cell functions.